Fumarate/ceramic composite based Scaffolds for tissue engineering: evaluation of hydrophylicity, degradability, toxicity and biocompatibility - Fernández, Juan Manuel (2014)
The present study was designed to investigate the possible cytotoxicity and biocompatibility of scaffolds based on previously characterized polymeric materials including poly- -caprolactone (PCL) or polydiisopropyl fumarate (blended or on their own), with or without hydroxyapatite (HAP). Water contact angle was also evaluated to determine the hydrophylicity of each scaffold. Degradation of different scaffolds was evaluated after a 10-week incubation in Dulbecco’s modified eagle medium (DMEM) supplemented with 5% (v/v) fetal bovine serum (FBS). Bone Marrow Stromal Cells (MSC) were grown on different scaffolds in an osteogenic medium, after which alkaline phosphatase activity (ALP) was evaluated. ALP activity increased when MSC were grown on PCL+HAP or Blend+HAP, as compared to PCL or Blend without HAP. The effect of different scaffolds on the proliferation of the macrophage cell line RAW 264.7, production of nitric oxide (NO) and secretion of pro-inflammatory cytokines was examined. After 72 h, macrophages proliferated equally well on all scaffolds, maintaining a rounded morphology. None of the investigated scaffolds induced production of NO or cytokine release into the culture media, suggesting an absence of cytotoxicity. Therefore, these polymer- and HAP-based scaffolds could potentially be used as bone substitute materials.